Cultural Differences in the Effect of an Explanation on Consumers' Perceived Justice and Post-Recovery Satisfaction / Boo Huey Chern and Ting Lee Hui - Boo, Huey Chern; Ting, Lee Hui (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
Service failure is an unavoidable reality faced by many service businesses today. A failure in service delivery leads to dissatisfied customer behaviors such as switching and spreading negative word-of mouth. Therefore, service providers need to be actively involved in returning customers' negative perceptions to a state of satisfaction. This study was conducted to speccally examine the effect of an explanation in mitigating the ill effect of unfavorable outcomes. In addition, the present study extended previous cultural research by focusing on the three major Eastern cultures (i.e., Chinese, Indian, and Malay/Muslim). The results of this study reveal that an explanation is associated with procedural justice. The provision of an explanation actually backfires in the Eastern cultures. Furthermore, perceived interactional justice and post-recovery satisfaction are lower among the Chinese than the Malay, while the Indian is indifferent. This study contributes to the cross-cultural relationship marketing literature. In addition, it is also provide guidance to industry practitioners in using this simplest and the most cost-effective tool as a service recovery initiative in managing customer perception.